Las Fortalezas abaluartadas de Mazagán, Ceuta y Diu. Ubicación y relación con el territorio. - Matos, João Barros (2018)
Las Fortalezas abaluartadas de Mazagán, Ceuta y Diu. Ubicación y relación con el territorio.